Study on Synthesis Method of Multipoint Seismic Waves for Buried Oil and Gas Pipeline in Shaking Table Tests - Jian-Bo Dai; Gui-Di Zhang; Cheng-Tao Hu; Kai-Kai Cheng (Shock and Vibration)
The buried oil and gas pipeline is a linear structure with infinite length. In the shaking table test of its seismic response, it is necessary to input the spatially related multipoint seismic wave considering the propagation characteristics of ground motion. The multipoint seismic excitation shaking table tests and loading scheme of buried oil and gas pipelines are designed and formulated. The synthesis method of spatial correlation multipoint seismic wave for the buried oil and gas pipeline test is proposed in this study. The values of relevant parameters are analyzed, and corresponding program is compiled by MATLAB. The results show that the developed multipoint excitation shaking table seismic wave input scheme is reasonable. At the same time, the synthesized multipoint seismic wave based on the actual seismic record and artificial random simulation seismic wave can meet the test requirements, which suggests the testing effect is good.